Study of causes and various modalities of management in postpartum hemorrhage at a tertiary care centre - Shivappa Marabasannanavar, Sneha; Tankasali, Manohar; Nagaraj, Mamatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum haemorrhage (PPH) remains a leading cause of maternal morbidity and mortality worldwide, particularly in low and middle-income countries. This study aimed to evaluate the causes and management strategies of postpartum haemorrhage at a tertiary care centre in India. Methods: This hospital-based case series study was conducted at S. Nijalingappa Medical College, Bagalkot, over 18 months from August 2022 to February 2024. The study included 35 cases diagnosed with postpartum haemorrhage, defined as blood loss ≥500 ml within 24 hours after vaginal birth or ≥1000 ml after caesarean delivery. Data was collected using a structured proforma through patient interviews and medical record reviews. Results: Most postpartum haemorrhage cases (65.7%) occurred in women aged 20-30 years and in primiparas (65.7%). Uterine atony was the leading cause (68.6%), followed by genital trauma (31.4%). Medical management with misoprostol (94.3%) and oxytocin (91.4%) was most common, along with carboprost (74.2%). Mechanical management included uterine massage (68.6%) and bimanual compression (57.1%). Surgical interventions included uterine artery ligation (28.6%), B Lynch sutures (20%) and obstetric hysterectomy (11.4%). Most patients (71.4%) had extended hospital stays exceeding 5 days. Conclusions: The findings emphasize the importance of having essential medications readily available and maintaining surgical expertise for managing severe cases. This study highlights the need for improved antenatal care, standardized management protocols, and early intervention strategies in similar healthcare settings.